1989
DOI: 10.1139/f89-179
|View full text |Cite
|
Sign up to set email alerts
|

Stream Temperatures and Inter-Annual Variability in the Emigration Timing of Coho Salmon (Oncorhynchus kisutch) Smolts and fry and Chum Salmon (O. Keta) Fry from Carnation Creek, British Columbia

Abstract: 1989. Stream temperatures and inter-annual variability in the emigration timing sf coho salmon (Onesrhyncdaus kisutch) smolts and .fry and churn salmon (0. keea) fry from Carnation Creek, British Columbia. Can. 8. Fish. Aquat. Sci. 46: 1396-1405 Variability in average stream temperatures between peak spawning and fry emergence accounted for 82 and 77% of the variance in the median emigration date sf fry of chum (Oncorhynchus keta) and coho salmon (0. kisutch), respectively, over a 9 to 10-yr period. The modele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 0 publications
3
41
0
Order By: Relevance
“…Female body size is positively related to fecundity and competitive ability, but these characteristics do not necessarily confer enhanced reproductive success in all situations (Fleming and Gross 1989;Holtby andHealey 1986, 1990;van den Berghe and Gross 1989). Selective harvest of large males could contribute to the observed size differences.…”
Section: Anecdotal Reportsmentioning
confidence: 99%
See 3 more Smart Citations
“…Female body size is positively related to fecundity and competitive ability, but these characteristics do not necessarily confer enhanced reproductive success in all situations (Fleming and Gross 1989;Holtby andHealey 1986, 1990;van den Berghe and Gross 1989). Selective harvest of large males could contribute to the observed size differences.…”
Section: Anecdotal Reportsmentioning
confidence: 99%
“…This result may reflect the tendency for the largest male smolts, typically the oldest, to return as jacks. Female fecundity increases greatly with increasing body size, but the same relation may not hold for males; in some situations small males or jacks can have high reproductive success (Holtby andHealey 1986, 1990). Males may forage in ways that reduce their risk of mortality rather than maximize their rate of growth, resulting in a size-at-age distribution that is skewed to smaller sizes relative to females (Holtby and Healey 1990) .…”
Section: Anecdotal Reportsmentioning
confidence: 99%
See 2 more Smart Citations
“…Holtby et al (1989) showed a strong positive relation between interannual spring stream temperature and median migration timing of coho salmon smolts. Relatively higher spring stream temperatures would result in higher potential growth rates in juvenile salmonids.…”
Section: Discussionmentioning
confidence: 94%